Advanced accounting 2016 : part 2 : based on Philippine financial reporting standards (PFRSs) - Millan, Zeus Vernon B. (Baguio City : Bandolin, Enterprise, 2016)
"This book is designed to provide an invaluable learning material for accounting student and CPA candidates." this book discusses and illustrates provisions of current financial reporting standards in a clear and easy-to-read manner. Practical insight on how the standards are applied in actual practice are provided as well."
Includes appendix and references.
English text.
Keywords: Accounting